Analisis Kinerja Keuangan Pemerintah Kota Sibolga Tahun 2018-2022 - Marbun, Vaulina; Deliana, Deliana; Nurlinda, Nurlinda (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
The Regional Revenue and Expenditure Budget (APBD) is an important document that reflects the plans and strategies of regional governments in managing finances and implementing programs and activities. Through the Regional Revenue and Expenditure Budget (APBD) regional governments not only plan their financial expenditure and receipts but also ensure transparency, accountability, and public supervision of the management of regional financial resources (Indonesia, 2019). The financial performance of regional governments is closely related to the region's ability to explore and manage original regional financial resources. This type of research is descriptive research. Data collection techniques in research use documentation and primary data techniques. The object of this research is the financial performance of the Sibolga City Government in 2018-2022. Financial performance analysis using ratios such as the financial independence ratio, fiscal decentralization ratio, flexibility ratio, and financial solvency ratio provides a comprehensive picture of the financial condition of an entity, especially local governments. ... From the research results, the conclusion is drawn that the financial performance of the Sibolga City Government in 2018-2022 is generally said to be quite good. Judging from the low financial independence ratio with an instructive relationship pattern, the fiscal decentralization ratio is lacking, the flexibility ratio is positive and the operational solvency ratio is good.